2022
DOI: 10.1186/s13071-022-05347-y
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole and aminoalcohol derivatives show in vitro anthelmintic activity against Trichuris muris and Heligmosomoides polygyrus

Abstract: Background Infections by gastrointestinal nematodes cause significant economic losses and disease in both humans and animals worldwide. The discovery of novel anthelmintic drugs is crucial for maintaining control of these parasitic infections. Methods For this purpose, the aim of the present study was to evaluate the potential anthelmintic activity of three series of compounds against the gastrointestinal nematodes Trichuris muris and Heligmosomoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The results of that study showed that BZD9 was the most effective compound, displaying a 50% inhibitory concentration (IC 50 ) value of 6 µM in eggs by the EHT [ 20 ]. Some of these compounds were also evaluated in two rodent models of other gastrointestinal nematodes, demonstrating that BZD09 effectively inhibited the motility of Heligmosomoides polygyrus adults at a concentration of 10 µM, while BZD15 inhibited Trichuris muris adult motility at the same concentration [ 54 ]. However, in the current study, none of these compounds exhibited activities exceeding 25% when tested against F. hepatica eggs at a concentration of 50 µM.…”
Section: Discussionmentioning
confidence: 99%

New benzimidazole derivative compounds with in vitro fasciolicidal properties

Valderas-García,
Castilla-Gómez de Agüero,
González del Palacio
et al. 2024
Parasites Vectors
Self Cite
“…The results of that study showed that BZD9 was the most effective compound, displaying a 50% inhibitory concentration (IC 50 ) value of 6 µM in eggs by the EHT [ 20 ]. Some of these compounds were also evaluated in two rodent models of other gastrointestinal nematodes, demonstrating that BZD09 effectively inhibited the motility of Heligmosomoides polygyrus adults at a concentration of 10 µM, while BZD15 inhibited Trichuris muris adult motility at the same concentration [ 54 ]. However, in the current study, none of these compounds exhibited activities exceeding 25% when tested against F. hepatica eggs at a concentration of 50 µM.…”
Section: Discussionmentioning
confidence: 99%

New benzimidazole derivative compounds with in vitro fasciolicidal properties

Valderas-García,
Castilla-Gómez de Agüero,
González del Palacio
et al. 2024
Parasites Vectors
Self Cite
“…Amino alcohols are functional groups commonly found in molecules associated with a range of biological activities. These include antimalarial, 22 anthelmintic, 23 cardioprotective, 24 antifungal 25 and antioxidative activities in vitro . 26 Moreover, these compounds have demonstrated in vitro antitumor potential, 27 the ability to inhibit human carbonic anhydrases, 28 antiproliferative activity against cervical, breast, and ovary cancer cells, 29 and potential in treating genetic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Among these heterocycles, benzimidazole stands out, as a purine-analog pharmacophore, with a very diverse therapeutic activity. The very broad spectrum of biological activities it treats include antimicrobial [4][5][6][7][8], antiviral [9,10], antihistamine [11,12], anticonvulsant [3,13], antitumor [14][15][16], proton pump inhibitors [17], antiparasitic [16,18,19], anti-inflammatory [20][21][22], or antihypertensive [23,24] activities. Some benzimidazoles are efficient agents in Diabetes mellitus [25][26][27], while astemizole compounds possess anti-prion activity to treat Creutzfeldt-Jakob disease [5,28].…”
Section: Introductionmentioning
confidence: 99%